Determining one-year trajectories of low back related leg pain in primary care patients: growth mixture modelling of a prospective cohort study - Ogollah, Reuben O.; Konstantinou, Kika; Stynes, Siobhán; Dunn, Kate M. (Wiley, 2018)
Objective